2002
DOI: 10.2337/diabetes.51.5.1346
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects on Age-Dependent Onset and Islet Cell Autoantibody Markers in Type 1 Diabetes

Abstract: Age-dependent associations between type 1 diabetes risk genes HLA, INS VNTR, and CTLA-4 and autoantibodies to GAD65 (GADAs), ICA512/IA-2, insulin, and islet cells were determined by logistic regression analysis in 971 incident patients with type 1 diabetes and 702 control subjects aged 0 -34 years. GADAs were associated with HLA-DQ2 in young but not in older patients (P ‫؍‬ 0.009). Autoantibodies to insulin were negatively associated with age (P < 0.0001) but positively associated with DQ8 (P ‫؍‬ 0.03) and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
198
6
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(247 citation statements)
references
References 59 publications
42
198
6
1
Order By: Relevance
“…Data on the effect of the CTLA4 gene region on beta cell autoimmunity are similarly ambiguous. The CTLA4-3′(AT)n microsatellite and the +49A/G polymorphism showed no association with humoral autoimmunity in Swedish and Belgian cohorts, whereas IA-2A showed association with the G allele of the +49A/G polymorphism in a Japanese study [7,24,25].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Data on the effect of the CTLA4 gene region on beta cell autoimmunity are similarly ambiguous. The CTLA4-3′(AT)n microsatellite and the +49A/G polymorphism showed no association with humoral autoimmunity in Swedish and Belgian cohorts, whereas IA-2A showed association with the G allele of the +49A/G polymorphism in a Japanese study [7,24,25].…”
Section: Introductionmentioning
confidence: 84%
“…An early study observed no association between the INS VNTR genotype and insulin-specific cellular and humoral autoimmunity [19], while class I alleles of the VNTR were found to contribute to the emergence of IAA in a larger case-control comparison [7]. It has also been suggested that the INS locus confers increased disease risk only in subjects with moderate-risk HLA genotypes [20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 DISS2: HLA genotyping for DQB1, DQA1 and DRB1 was performed with PCR amplification followed by dot blot hybridizations and by restriction fragment length polymorphism as previously described, 13 except that allele-specific PCR amplification (PCR-SSP) of DRB1 alleles was also used. 40 BDD: A method based on an asymmetrical PCR and a subsequent hybridization of allele-specific probes was used, as described previously.…”
Section: Genotyping Methodsmentioning
confidence: 99%
“…11 The HLA association to T1D is also known to vary with age at onset, such that the association is stronger in younger patients compared with older patients. 3,12,13 Genome-wide significant association to celiac disease has recently been reported for markers in the CIITA gene. 14 In addition, increased susceptibility to myocardial infarction (MI), rheumatoid arthritis (RA) and multiple sclerosis (MS) has been demonstrated for a polymorphism (rs3087456) in the 5 0 region of type III CIITA.…”
Section: Introductionmentioning
confidence: 99%